1996
DOI: 10.1507/endocrj.43.221
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors (IGFs) and IGF-Binding Proteins (IGFBP-1, -2 and -3) in Diabetic Pregnancy: Relationship to Macrosomia.

Abstract: Abstract.To evaluate the role of insulin-like growth factors (IGFs) and IGF-binding proteins (IGFBPs) in exessive fetal growth (macrosomia) in diabetic pregnancy, 84 insulin-treated diabetic mothers and their infants were tested for serum concentrations of IGF-I, IFG-II, and IGFBP-1, -2 and -3. These parameters were correlated with the birth weight of neonates and placental weight. IGF-I and II levels were determined by specific radioimmunoassays (RIAs) after serum samples were extracted with aid-ethanol. IG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…We have shown that concentrations of IGF-I and IGF-II in the cord blood of the newborns of diabetic mothers are higher than in infants born to normal mothers [4]. Furthermore, there was a positive correlation between the cord IGF-I or IGF-II level and birth weight of newborns, suggesting that both IGF-I and IGF-II are involved in fetal growth, but the role of IGFs and their binding proteins produced in placental tissues in regulating human fetal or placental growth is unknown.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…We have shown that concentrations of IGF-I and IGF-II in the cord blood of the newborns of diabetic mothers are higher than in infants born to normal mothers [4]. Furthermore, there was a positive correlation between the cord IGF-I or IGF-II level and birth weight of newborns, suggesting that both IGF-I and IGF-II are involved in fetal growth, but the role of IGFs and their binding proteins produced in placental tissues in regulating human fetal or placental growth is unknown.…”
mentioning
confidence: 86%
“…RNAs of IGF-I, IGF-II and all species of IGFBPs (IGFBP- [1][2][3][4][5][6] were expressed in human placenta.…”
Section: Messengermentioning
confidence: 99%
“…Several studies investigated the associations of IGF-I and IGFBPs in maternal plasma in pregnancies complicated with DM. Maternal IGF-I was decreased in diabetic pregnancies [95], whereas fetal IGF1 serum levels were increased in infants of mothers with T1DM and T2DM compared to non-diabetic controls [96]. Higher levels of IGFBP3 were observed in both maternal and fetal serum in T1DM pregnancies compared to non-diabetic controls, probably due to increased proteolysis in maternal but not in fetal serum [93].…”
Section: Human Placental Growth Hormone (Pgh)-igf Axis and Fetal Growthmentioning
confidence: 99%
“…However, cord serum IGFBP-1 measure-ments have yielded inconsistent results in diabetic pregnancies, i.e. both low [14] and high [15] levels have been found, with no association with birth weight. These studies relied on assays with unknown specificities for the different IGFBP-1 phosphoisoforms.…”
Section: Introductionmentioning
confidence: 99%